PROPERTIES OF HYBRID HYDROGELS WITH THE ADDITION OF MODIFIED STARCH AND MONTMORYLONITE-TYPE CLAY - ЛЯШОК, І. О.; ПЛАВАН, В. П.; ІЩЕНКО, О. В.; ГОДУНКО, А. А.; ШВЕЦЬ, В. В. (Technologies and Engineering, 2023)
Purpose. The aim of the scientific work is to develop the technology for obtaining hybrid hydrogel materials based on the polymer composition of polyvinyl alcohol with the addition of modified starch and montmorillonite-type clay and to study their sorption properties. Methodology. A mixture of 10% solution of polyvinyl alcohol (PVA) and 5% solution of carboxymethylated starch (СMS) in a ratio of 1:1 was used to create the basis of hybrid hydrogel materials. As a filler for hydrogels, montmorillonite-type clay was used in the form of powder in the amount of 1 to 10 parts by volume. Hybrid hydrogels were obtained by single freezing for 24 hours at a temperature of -15 oC, as a result of which cryostructuring took place. The moisture content of the hydrogel materials was determined on a MA-50 R Radwag moisture analyzer at a temperature of 70 oC. To assess the effect of the amount of montmorillonite-type clay in the PVA/СMS composition on the properties of hybrid hydrogel materials, the sorption characteristics of the compositions were studied by the gravimetric method. Findings. The technology for obtaining hybrid hydrogel materials by the cryostructuring method has been developed. As a result of the analysis of the sorption properties of hybrid hydrogel materials, it was established that the introduction of montmorillonite-type clay leads to a complete change in the nature of the sorption curves. Collapse of hydrogel systems is observed, and sorption drops from 1000% to 250%, reaching an equilibrium value within 72 hours. At the content of 1 volume part of clay, sorption decreases by 270% and is 720% in the equilibrium state. The maximum decrease in sorption by 480% is observed for samples that contain 5 volume parts of clay and is 300% in the equilibrium state. When studying the desorption of hybrid hydrogel materials, it was established that the addition of montmorillonite-type clay slows down the desorption process of hydrogels based on PVA/СMS. It was found that polymer compositions based on PVA with carboxymethylated starch in a ratio of 1:1 with the addition of clay in the amount of 1–2 parts by volume can be recommended for obtaining cryohydrogels with increased sorption properties and slower drying speed. Originality consists in determining the effect of adding montmorillonite-type clay to a composition based on PVA with СMS for obtaining hydrogels by the cryostructuring method. It was established that the addition of clay leads to the collapse of hybrid hydrogel materials under the influence of water, and to the slowing down of the desorption properties of hybrid hydrogels. Practical value. The technology for obtaining hybrid hydrogel materials based on a mixture of polyvinyl alcohol and carboxymethylated starch with the addition of montmorillonite-type clay by the cryostructuring method was developed, and the possibility of adjusting the sorption properties of hydrogels by introducing clay was determined.